Development for Department Chairs: Why Fundraising is Now Part of the Job - Craig D Hlavac (Academic Chairpersons Conference Proceedings, 2019)
Development in higher education is often used synonymously with fundraising – and many believe both are relegated to the Office of Institutional Advancement and perhaps the Deans. However, the work of development in the contemporary university is quickly becoming everyone’s responsibility – including Department Chairs. While many chairs may have experience in writing grants to bring in revenue, the skills required to work with prospective donors are quite different. This session will provide all chairs with tools and resources focused on fundraising for the academic department. Donor relations, building a relationship with Institutional Advancement, and developing a department-based advisory board will all be discussed.
Keywords: Development; Fundraising; Institutional Advancement; Leadership